Sámi báikenamat, válddi relašuvnnat ja representašuvdna - Rautio Helander, Kaisa (Sámi dieđalaš áigečála, 2026)
A representation is a set of practices by which meanings are constituted and communicated. Representations not only reflect reality, but they help to constitute reality. Hence the representation is often deliberately built up or constructed to give a socially and politically defined image of the society. The crucial question is who has the power of building up, deciding and keeping the representation. Historically, Western eurocentric representations connected to colonial power relations and also to strong nation states have mostly imposed the power relations and affected image and understanding of the world. In my paper, I will discuss how indigenous place names have historically been treated in forming a deliberate representation. Colonial naming and renaming practices in indigenous areas are defined as toponymic colonialism by late J. B. Harley (2001: 181). As shown in this paper, the similar renaming practices can also be found in the Western nation states when deliberately supressing indigenous toponymy during the nation building process. The history of Norwegian toponymic policy is used as an example of processes of toponymic colonialism in a Western nation state. The paper will exemplify strategies of silencing and subjugation of indigenous place names which are used to construct and to keep the representation. The historical legacy of the toponymic colonialism still affects especially the current linguistic landscape in many indigenous areas. A long-standing use of only majority toponymy and silencing indigenous names, especially settlement names such as village and town names in signing, have significally strengthen the monolingual representation which has been built up during a long time. Hence, the current decolonization process in aiming to an equal multilingual use of toponymy in official contexts, still meets harsh opposing which keeps the status quo of the present representation. This shows that the toponymic colonialism is not just a historical phenomenon but rather has changed to toponymic neocolonialism in the contemporary situation.